Synthesis of arachidonate cyclo-oxygenase products by rheumatoid and nonrheumatoid synovial lining in nonproliferative organ culture. Issue 1 (February 1983) - Salmon, J. A.; Higgs, G. A.; Vane, J. R.; Bitensky, Lucille; Chayen, J.; Henderson, B.; Cashman, B.
Abstract : Specimens of human rheumatoid and nonrheumatoid synovial lining were maintained in nonproliferative organ culture for 20 hours. The culture fluids were then assayed for prostaglandin E2 (PGE2 ), thromboxane B2 (TXB2 ), and 6-keto-prostaglandin F1α (6-keto-PGF1α ) by specific radioimmunoassay. The presence of each of these substances was confirmed by gas chromatography and mass spectrometry. Rheumatoid tissue produced significantly more of each cyclo-oxygenase product than nonrheumatoid tissue.